PENGARUH LAPISAN SERAT dan RESIN EPOXY terhadap KEKUATAN UJI IMPACT KOMPOSIT SERAT ECENG GONDOK - Zidan Septian Adisurya; Priyagung Hartono; Cepi Yazirin (Universitas Islam Malang, 2023)
A composite is a material structure formed from a combination of two or more materials, processed on a macroscopic scale and physically fused. To improve the characteristics of natural fibers in composites, a NaOH alkalization process is carried out which influences the fiber composites. Real experimental strength of the composite. The results showed that Alkalization of NaOH in water hyacinth fiber with variations in resin and fiber fractions (40%, 50%, 60%) and concentration (5% and 10%) affected the impact value. Specimens with a 60% resin and fiber fraction that experienced 5% alkalization showed the lowest impact, while a 40% resin and fiber fraction that experienced 10% alkalization had the highest impact. These findings indicate that NaOH alkalization significantly affects water hyacinth fibers, potentially increasing strength due to the removal of lignin, hemicellulose, and pectin. Loss of these components can make the fiber more brittle and susceptible to damage. In testing the resin and fiber fractions (40%, 50%, 60%) with varying concentrations (5% and 10%) when mixing fiber with matrix, it was found that the 60% resin and fiber fraction with a concentration of 5% had the lowest impact strength of 61 J/mm2, while the resin and fiber fraction of 40% with a concentration of 10% has the highest strength of 82 J/mm2. The results of this research highlight the importance of optimizing the volume fraction of fiber and epoxy matrix to improve the impact characteristics of water hyacinth fiber composites.Keywords: composite, alkalization, volume fraction, fiber, water hyacinth